ANALISIS KEMAMPUAN BERCERITA SISWA KELAS IV SDN 4 KERTOSARI KABUPATEN KENDAL - Aditya Aris Pangestu; Mei Fita Asri Untari; Ikha Listyarini (STKIP Subang, 2023)
This study aims to determine and analyze the storytelling skills of students. This type of research is qualitative research. Sources of data used are interviews, observation and documentation. The problem in this study is how the storytelling ability of class students. The results of this study showed that there were 30 students' storytelling abilities, most students around 60% or 18 students were able to tell stories fluently. The child's pronunciation when telling stories is good, the fluency when telling stories is quite good, the style of expression is sufficient, the students' appreciation of the story is sufficient and the mastery of the contents of the story is carried out according to the storyline well. About 40% or 12 students have not been able to meet the set storytelling criteria, namely students are only able to read stories with a little spelling, with a flat style/expression, appreciation that has not yet appeared, pronunciation that is not clear and by reading without paying attention to the appreciation of the story.